Study of Solubility of Urinary Stone in both Natural-Fresh Juice and Acid-Hydrolyzed Juice of Samras (Ribes grossubaria) Fruit - Rani Sinha, Madhu; Dev, Avnisha; Tagore, R.N. (Asian Journal of Chemistry, 2010)
Urolithiasis is associated with alteration in micro-environment integrity of urine. High citrate content diet deliver high alkali load and hence reduce the risk of formation of urinary stone. The hardness of urinary stones varies from stone to stone, depending on size and their chemical compositions. The solubility of urinary stones of different forms (whole and powder) in naturalfresh juice and in acid-hydrolyzed juice of samras (Ribes grossubaria) fruit has been investigated. The solubility efficiency was studied. This study showed that the solubility of powdered form of urinary stone was much higher than the single whole stone and comparatively much higher in acid-hydrolyzed juice than non-hydrolyzed juice i.e., natural-fresh juice of same fruits. This short term study suggests that acid-hydrolyzed formulation of fruits juice would be helpful in designing of herbal preparation for dissolving, at least partially 'the urinary stones'. However, additional studies are needed to evaluate the role of fruit's juice of samras (Ribes grossubaria) in long-term preventive and therapeutic management of urolithiasis.